2014
DOI: 10.1021/ma5015353
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Approach to Accurately Predict the Complex Molecular Weight Distribution in the Polymerization of Strainless Cyclic Esters

Abstract: Polyesters obtained by the catalytic ringopening polymerization of macrolactones in many aspects resemble the properties of polyethylene. However, the molecular weight distribution is intrinsically different and equals the molecular weight distribution observed for a stepgrowth process even though macrolactone ring-opening polymerization follows a chain-growth mechanism. The concurrent occurrence of transesterification reactions leading to the formation of cyclic polymers is responsible for the deviation from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 35 publications
3
53
0
Order By: Relevance
“…These cyclic oligomers are present in excess compared to their low molecular weight linear counterparts. 15,34 However, it is peculiar that this transesterification does lead to cyclic PPDL and PLLA, but not to cyclic copolymers consisting of a combination of PDL and LLA. For example, a peak is present at 1706.1 g·mol , which corresponds to cyclic (PDL) 7 + Na + , while there is no peak present at 1706.1 + x72.06 g·mol −1 (x lactidyl units).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cyclic oligomers are present in excess compared to their low molecular weight linear counterparts. 15,34 However, it is peculiar that this transesterification does lead to cyclic PPDL and PLLA, but not to cyclic copolymers consisting of a combination of PDL and LLA. For example, a peak is present at 1706.1 g·mol , which corresponds to cyclic (PDL) 7 + Na + , while there is no peak present at 1706.1 + x72.06 g·mol −1 (x lactidyl units).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…9 The formed macrocyclic PPDL will also undergo ring-opening again and it is therefore the balance between cyclization reactions and ROP reactions that will yield the equilibrium concentration of the cyclic chains. 15 After the addition of lactide, the linear PPDL chains initiate the polymerization of LLA forming the poly(PDL-block-LLA) copolymer. From the moment one LLA monomer has been inserted, only LLA monomers can be polymerized or PLLA fragments transesterified.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In earlier work it was shown that the conversion of Amb could quantitatively be determined using low-MW-SEC analysis. 40 Therefore, here we followed a similar approach for the polymerization of Amb, S1, and S2. Using this method, the conversion is defined as the disappearance of the monomer and not as the fraction of opened macrolactone rings.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Consequently, the vast majority of the chains in the low molecular weight regime will be cyclics. 40 As a result of the lower average molecular weight of P(S2), besides cyclics, a number of distributions corresponding to linear chains can be identified. All distributions have a repeating unit of 386 g mol −1 equivalent to the molecular weight of S2.…”
Section: ■ Introductionmentioning
confidence: 99%